2017
DOI: 10.1111/1462-2920.13665
|View full text |Cite|
|
Sign up to set email alerts
|

Symbiotic bacteria associated with a bobtail squid reproductive system are detectable in the environment, and stable in the host and developing eggs

Abstract: Female Hawaiian bobtail squid, Euprymna scolopes, have an accessory nidamental gland (ANG) housing a bacterial consortium that is hypothesized to be environmentally transmitted and to function in the protection of eggs from fouling and infection. The composition, stability, and variability of the ANG and egg jelly coat (JC) communities were characterized and compared to the bacterial community composition of the surrounding environment using Illumina sequencing and transmission electron microscopy. The ANG bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
87
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(98 citation statements)
references
References 53 publications
9
87
1
Order By: Relevance
“…In the field of microbial symbiosis, significant interest focuses on community-level structure and on distinguishing the contributions of different species within complex hostassociated microbiomes [1][2][3][4][5]. Recently, an awareness of the importance of strain-level differences occurring within a colonizing bacterial species in such communities has emerged [1,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of microbial symbiosis, significant interest focuses on community-level structure and on distinguishing the contributions of different species within complex hostassociated microbiomes [1][2][3][4][5]. Recently, an awareness of the importance of strain-level differences occurring within a colonizing bacterial species in such communities has emerged [1,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The bobtail squid, Euprymna scolopes , is endemic to the Hawaiian archipelago and relies on the well-studied light organ symbiont Vibrio fischeri to avoid predation ( 1 ). In addition to this symbiosis, adult females also harbor a complex bacterial consortium in their reproductive system ( 2 , 3 ). The accessory nidamental gland (ANG) is conserved throughout many species of squid, cuttlefish, and bobtail squid ( 4 ) and was first described over a century ago ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Not just host-encoded factors but also resident microbes play important roles in shaping host-microbe interactions, as illustrated by the talk from Spencer Nyholm (University of Connecticut, Storrs, CT), "The Hawaiian Bobtail Squid as a Model for Studying Defensive Symbioses and Development." In studying the microbiome of the accessory nidamental gland (ANG), a reproductive organ in female cephalopods, including the bobtail squid (Euprymna scolopes), he showed that the ANG is packed with a diverse consortium of bacteria (20,21). The ANG sits adjacent to the oviduct, and as eggs pass by the gland, bacteria are deposited into the developing jelly coat layer.…”
Section: Meeting Reviewmentioning
confidence: 99%